Nonsacrificial Nitrile Additive for Armoring High‐Voltage LiNi0.83Co0.07Mn0.1O2 Cathode with Reliable Electrode–Electrolyte Interface toward Durable Battery. Issue 30 (5th July 2022) - Li, Xin; Han, Xinpeng; Li, Gang; Du, Juan; Cao, Yu; Gong, Haochen; Wang, Huili; Zhang, Yiming; Liu, Shuo; Zhang, Baoshan; Liu, Xinying; Khangale, Phathutshedzo; et al.
Abstract: High‐capacity Ni‐rich layered oxides are considered as promising cathodes for lithium‐ion batteries. However, the practical applications of LiNi0.83 Co0.07 Mn0.1 O2 (NCM83) cathode are challenged by continuous transition metal (TM) dissolution, microcracks and mixed arrangement of nickel and lithium sites, which are usually induced by deleterious cathode–electrolyte reactions. Herein, it is reported that those side reactions are limited by a reliable cathode electrolyte interface (CEI) layer formed by implanting a nonsacrificial nitrile additive. In this modified electrolyte, 1, 3, 6‐Hexanetricarbonitrile (HTCN) plays a nonsacrificial role in modifying the composition, thickness, and formation mechanism of the CEI layers toward improved cycling stability. It is revealed that HTCN and 1, 2‐Bis(2‐cyanoethoxy)ethane (DENE) are inclined to coordinate with the TM. HTCN can stably anchor on the NCM83 surface as a reliable CEI framework, in contrast, the prior decomposition of DENE additives will damage the CEI layer. As a result, the NCM83/graphite full cells with the LiPF6‐EC/DEC‐HTCN (BE‐HTCN) electrolyte deliver a high capacity retention of 81.42% at 1 C after 300 cycles at a cutoff voltage of 4.5 V, whereas BE and BE‐DENE electrolytes only deliver 64.01% and 60.05%. This nonsacrificial nitrile additive manipulation provides valuable guidance for developing aggressive high‐capacity Ni‐rich cathodes. Abstract : In this work, 1, 3, 6‐hexanetricabonitrile (HTCN) and 1, 2‐Bis(2‐cyanoethoxy)ethane (DENE) as electrolyte additives for NMC83/graphite cells are introduced. Structural characterization and compositional analysis demonstrate that HTCN electrolyte additive can tightly anchor at the NCM83 surface without decomposition by its three CN functional groups to construct a uniform and robust cathode electrolyte interface layer at a high voltage.